Structural insights into the catalytic mechanism of sphingomyelinases D and evolutionary relationship to glycerophosphodiester phosphodiesterases - Murakami, M. T.; Fernandes-Pedrosa, M. F.; de Andrade, S. A.; Gabdoulkhakov, A.; Betzel, C.; Tambourgi, D. V.; Arni, R. K. (Elsevier B.V., 2006)
Spider venom sphingomyelinases D catalyze the hydrolysis of sphingomyelin via an Mg2+ ion-dependent acid-base catalytic mechanism which involves two histidines. In the crystal structure of the sulfate free enzyme determined at 1.85 angstrom resolution, the metal ion is tetrahedrally coordinated instead of the trigonal-bipyramidal coordination observed in the sulfate bound form. The observed hyperpolarized state of His47 requires a revision of the previously suggested catalytic mechanism. Molecular modeling indicates that the fundamental structural features important for catalysis are fully conserved in both classes of SMases D and that the Class II SMases D contain an additional intra-chain disulphide bridge (Cys53-Cys201). Structural analysis suggests that the highly homologous enzyme from Loxosceles bonetti is unable to hydrolyze sphingomyelin due to the 95G1y -> Asn and 134Pro -> Glu mutations that modify the local charge and hydrophobicity of the interfacial face. Structural and sequence comparisons confirm the evolutionary relationship between sphingomyelinases D and the glicerophosphodiester phosphoesterases which utilize a similar catalytic mechanism. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Sphingomyelinase D; catalytic mechanism; Mg2+-binding site; hydrodynamic behavior; Crystal structure; glycerophosphodiester phosphodiesterases